Pengaruh Kinerja Keuangan, Ukuran Perusahaan terhadap Struktur Modal - Chorina Elsa Fatika; Suhendro Suhendro; Anita Wijayanti (Ekonomis: Journal of Economics and Business, 2020)
The purpose of this study is to examine and analyze the factors that influence the capital structure. The independent variables in this study are profitability, liquidity, asset structure, and company size. The population in this study are food and beverage companies listed on the Indonesia Stock Exchange for the period 2015-2018. The sample selection technique used in this study was purposive sampling and 10 company samples were obtained. The analytical method used in this study is multiple linear regression. The results of this study simultaneously show that profitability, liquidity, asset structure, and company size significantly influence the capital structure. The results of the research partially show that profitability, liquidity and firm size affect the capital structure, asset structure does not affect the capital structure.